Therapeutic area variability in the collection of data supporting protocol end points and objectives. (February 2014) - Getz, Kenneth; Stergiopoulos, Stella
More than 22, 000 procedures from 116 protocols were classified according to the end points and objectives that they support and their direct costs were determined. The distribution of procedure classifications and costs for four therapeutic areas – oncology, endocrinology, CNS and anti-infectives – were analyzed and substantial variability was observed. Endocrine and anti-infective protocols contained a high relative average number of supplementary, tertiary and exploratory (i.e., 'non-core') end points. Oncology and CNS protocols had the highest relative proportion of procedures supporting 'core' end points and objectives and lower relative proportions of those supporting 'non-core' end points. The relative proportion of direct costs to administer endocrine protocol procedures supporting 'non-core' end points and objectives was significantly higher than that of other therapeutic areas. The results of this study provide important benchmarks by therapeutic area to help clinical teams optimize protocol design.